2014
DOI: 10.1111/1556-4029.12623
|View full text |Cite
|
Sign up to set email alerts
|

Human Fatality Due to Thallium Poisoning: Autopsy, Microscopy, and Mass Spectrometry Assays,

Abstract: Thallium has been responsible for many intoxications since its discovery; however, toxicological profiles for thallium in human fatalities have not been updated recently. Autopsy, microscopic investigations, and toxicological analyses were performed on a married couple who died from thallium sulfate intended homicidal poisoning. The distribution of thallium was established by inductively coupled plasma mass spectrometry with hair samples showing the highest thallium concentration. Electron microscopy revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…Less commonly, hair loss following thallium exposure may occur over a shorter time course. For example, Li et al [5] reported the start of hair loss in a 49-year-old female 7 days after the onset of polyneuropathy following malicious thallium poisoning. Namba et al [11] also reported hair loss 1 week after the ingestion of thallium in 3 out of 5 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less commonly, hair loss following thallium exposure may occur over a shorter time course. For example, Li et al [5] reported the start of hair loss in a 49-year-old female 7 days after the onset of polyneuropathy following malicious thallium poisoning. Namba et al [11] also reported hair loss 1 week after the ingestion of thallium in 3 out of 5 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic examination of anagen hairs should reveal tapered, pigmented hair bulbs, with attached root sheathes, as compared to telogen hairs which demonstrate a club-shaped bulb with no pigment or root sheath [64]. Multiple cases involving thallium, colchicine, and selenium toxicity report anagen hairs with or without dystrophic follicles on trichoscopy, light microscopy, and scanning microscopy [5, 6, 31, 37, 42, 64-66]. Unfortunately, many reported cases did not initially present to dermatology and microscopic examination of the hair was not completed.…”
Section: Discussionmentioning
confidence: 99%
“…Thallium is a toxic "heavy metal" [15] that can be found in low concentrations [16] in several minerals of the Earth crust [13] and used in many industries: bijous [17], photography and optical lenses [18], dyeing and pigments [17], concrete industries [6], waxing products [19] and for green fireworks [20] that take advantage of the spectral emissions of this element [21].…”
Section: Discussionmentioning
confidence: 99%
“…Cheiloscopy (lip morphology and thickness) and smile photograph analysis deals with the study of elevations and depressions which form a characteristic pattern on the external surface of the lips are also used to determine age and gender in forensic dentistry [2,14,[21][22][23]. Because teeth can be an important deposit of exogenous substances accumulated both in the pulp and in the calcified tissues, they are an invaluable source of data from a toxicological point of view [24]. Substantial postmortem changes elude accurate estimate of the time of death.…”
mentioning
confidence: 99%